Analisis Kohesi Leksikal pada Berita Olahraga di Surat Kabar Solopos Edisi Oktober 2019 - Siti Aminataz Zuhriyah (ESTETIK : Jurnal Bahasa Indonesia, 2020)
The study entitled "Analysis of Lexical Cohesion in Sports News in the October 2019 Solopos Newspaper" aims to describe or analyze lexical cohesion contained in the October edition of the Solopos newspaper. The method used in this study is a descriptive qualitative method. This method is a research method that seeks to describe objects according to their actual circumstances. There are five stages in this study, namely the stages of reading newspaper texts, coding the data in accordance with the theory, identifying, clarifying, and concluding and presenting data. The data of this study is a collection of the October 2019 edition of the Solopos rubric soccer newspaper. The results of this study indicate that of the six types of lexical cohesion that are often found in Solopos newspapers are repetition or iteration